2019
DOI: 10.1037/men0000170
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the muscular ideal on appearance-related attentional biases in men.

Abstract: Limited research has investigated appearance-related attentional biases in men. This study examined the effects of priming on attentional biases in men and whether the biases were associated with body image. The dot-probe task (DPT), a commonly used reaction time based measure, was adapted to include images between each trial of the task to test the effects of these images on attentional biases for appearance-related word stimuli. Men (N = 60) completed body image questionnaires online and attended a laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Boothroyd et al (2012) propose that as well as visual diet influencing what is considered normal, achievable, and attractive, we associate high muscularity with good health and high socioeconomic status through associative learning mechanisms, and that both influences may act in parallel. Therefore, the wealth of information portraying masculinity and muscularity as desirable can lead to internalisation of these ideals through the visual diet hypothesis and associative learning mechanisms, and when ideal muscularity is not achieved, this can lead to negative outcomes such as BID, disordered eating (Lane, Mulgrew, White, & Mahar, 2019), and health-risking behaviours such as steroid use (Litt & Dodge, 2008). Jones and Crawford (2005) found that body image issues develop in boys between the ages of 13 and 16, with older boys reporting more body-focussed discussion with peers.…”
Section: Male Body Image and Muscularitymentioning
confidence: 99%
See 1 more Smart Citation
“…Boothroyd et al (2012) propose that as well as visual diet influencing what is considered normal, achievable, and attractive, we associate high muscularity with good health and high socioeconomic status through associative learning mechanisms, and that both influences may act in parallel. Therefore, the wealth of information portraying masculinity and muscularity as desirable can lead to internalisation of these ideals through the visual diet hypothesis and associative learning mechanisms, and when ideal muscularity is not achieved, this can lead to negative outcomes such as BID, disordered eating (Lane, Mulgrew, White, & Mahar, 2019), and health-risking behaviours such as steroid use (Litt & Dodge, 2008). Jones and Crawford (2005) found that body image issues develop in boys between the ages of 13 and 16, with older boys reporting more body-focussed discussion with peers.…”
Section: Male Body Image and Muscularitymentioning
confidence: 99%
“…Body Image Dissatisfaction (BID) is an issue whereby individuals perceive their own body to be in some way different from the body size or shape they wish to have and feel emotional dissatisfaction or distress at that discrepancy (Cash, Morrow, Hrabosky, & Perry, 2004). For women, their desired body is often thinner than their current body, in line with the hyper-thin ideal presented by Western media (Ball & Dittmar, 2011;Boothroyd, et al, 2016;Juarascio, et al, 2011), while men aspire for a more muscular body (Grossbard, Neighbors, & Larimer, 2011;Lane, Mulgrew, White, & Mahar, 2019;Thornborrow, Onwuegbusi, Mohamed, Boothroyd, & Tovee, 2020). BID emerges early in girls (Evans, 2012;Evans, et al, 2017) and is prevalent in both sexes by puberty, with 24-80% of early adolescent girls (Bornioli, Lewis-Smith, Smith, Slater, & Isabelle, 2019;Dion, et al, 2015;Stice & Whitenton, 2002) and 14-54% of boys (Bornioli et al, 2019;Dion, et al, 2015; expressing dissatisfaction.…”
Section: Introduction Body Imagementioning
confidence: 99%
“…The second pathway includes the prevention of the initial occurrence of sociocultural processes that contribute to poor body image outcomes. Indeed, experimental studies have demonstrated that exposure to muscular and lean male bodies, through a number of communication mediums, is associated with increases in overall body dissatisfaction (Murnen & Karazsia, 2017), muscular dissatisfaction (Galioto & Crowther, 2013; Lane et al, 2019), and body fat dissatisfaction (Tylka, 2011). Such findings suggest that exposure to idealized body shapes in society may lead to increased perceived pressure to achieve this physique, and that esthetics rather than functional qualities are highly regarded within the contemporary male culture.…”
mentioning
confidence: 99%